Alba Valdez: a palavra das mulheres na história da literatura e da imprensa cearense - Souza, Keyle Samara Ferreira de (2019)
The actual research aimed to track back the process of inclusion of the writer, journalist and teacher Alba Valdez in the history of Literature and Press in Ceará. We analyzed the literary and journalistic writing of women in Ceará during the 19th and 20th centuries. For this, we proposed to revisit the history of women through Perrot (1991, 1998, 2005), Käppeli (1991), Falci (2011), D'incao (2011), paralleling the reality of women in Ceará , above all in the same time frame, going back to the process of conquering the public space by these women through the literary writing in the Ceará newspapers, as well as recognizing the press as a place of women's words in Ceará, based in Ketterer ( 1996), Cunha (2008), Duarte (2016), and in Valdez's own speeches and memoirs (1907, 1937), as well as in the nineteenth and twentieth-century newspapers. This led us to revisit the history of the women's press in that state, which enabled us to go beyond organizing a list of edited periodicals and / or intended for the female audience, but to investigate the participation and performance of women throughout the press between the end of the eighteenth and mid-twentieth centuries. In this endeavor, we prioritize the search of primary sources, periodicals and documents. In this way, we first contextualize the writing of women in Ceará, in order to understand the social place of Alba Valdez in the history of literature and the press supported by the theories of Certeau (2011). This, starting with newspaper clippings and memorialist productions, considering them as documentary sources, restored the life story of Alba Valdez, in a process similar to that described by Chartier (1990; 2011) and Lacerda (2003). Therefore, we deduce that in the bibliographical trajectory of Alba Valdez the publication in the periodicals, that became important networks of sociabilities, in accordance with Sirinelli (1996), Teixeira (2011), Schueler (2018) predominated, as well as we can conceptualize the associations literary and intellectual writings that enabled women of letters, such as Alba Valdez, to publish what they wrote, expressing their thoughts, feelings and opinions. From this perspective, the comparison of newspapers, magazines and almanacs allowed us to identify, reunite and reorganize the work of Alba Valdez, reworking her work through her writings, in such a way that we find unpublished works by the author, which enabled us to build a new biographical trajectory of this writer, recognizing that the periodicals were much more than textual supports, as advocated by Barbosa (2007) and Luca (2014, 2015), being constituted as determinants in the production of literary writing and means of sociability for literature of feminine authorship.